If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -162 + -7x = 2x + 63 Reorder the terms: -162 + -7x = 63 + 2x Solving -162 + -7x = 63 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -162 + -7x + -2x = 63 + 2x + -2x Combine like terms: -7x + -2x = -9x -162 + -9x = 63 + 2x + -2x Combine like terms: 2x + -2x = 0 -162 + -9x = 63 + 0 -162 + -9x = 63 Add '162' to each side of the equation. -162 + 162 + -9x = 63 + 162 Combine like terms: -162 + 162 = 0 0 + -9x = 63 + 162 -9x = 63 + 162 Combine like terms: 63 + 162 = 225 -9x = 225 Divide each side by '-9'. x = -25 Simplifying x = -25
| 9=13-s | | 11-(12-5)= | | 3x-2(6x-10)=-6+3(5x+4) | | 5*+11=18 | | -6x-7-5x=-73 | | s^2-16s+80=0 | | 2x(3x+1)-6x^2=4 | | 4a+3(a+2)=2(3a+2) | | 7-3(x)=12 | | 8+p=25 | | .05+25=3.00 | | [8w+8]=21 | | 41/5/3/5 | | 3(x+4)=x/2-8 | | -5x=-6-y | | 3y+y=12-5 | | 2=15-q | | (X/7)-6=36 | | 1-7b=-8(1+2b) | | -5/6q-(q-1)=1/4(-9+80) | | (3x-7)=(9x-5) | | 1/2x-3=5/8x | | 7(x+3)-1=5(x+4)+10 | | 5x^2+2x-192=0 | | 2t-6=9 | | 10+y=13 | | -12x+4y=-20 | | x-5=2(4x-3) | | 2.5/10=x/12 | | -13=5(1+4m)-3 | | 13-12x=2y | | -123+12x=x+108 |